2016
DOI: 10.1155/2016/7258313
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ammonia in Synthesis of Silver Nanoparticles in Skim Natural Rubber Latex

Abstract: Silver nanoparticles (AgNPs) were synthesized in skim natural rubber latex, the by-product from concentrated latex production. The role of ammonia was investigated by varying the concentration to be 0.217, 0.362, 0.377, 0.392, and 0.406 wt%. The emergence of AgNPs was detected by UV-visible spectrophotometer and electrical conductivity meter. Upon increasing ammonia concentration, the ABS peak increased to a maximum and slightly shifted to a higher wavelength and then it decreased afterward and slightly shifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Generally, it was noted that the silver ions favoured a linear structural geometry because of the lack of a stereochemical www.nature.com/scientificreports/ directionality which is formed from the d 10 configuration and a relatively weak nature of the silver(I)-ligand bonds 74 . Hence, the most stable geometrical structure was seen to have a linear geometry 75 as the ground and the excited state energies for this geometrical structure were very stable 76 . In this case, one Ag ion was donated to the Cd 2+ ions.…”
Section: +mentioning
confidence: 97%
“…Generally, it was noted that the silver ions favoured a linear structural geometry because of the lack of a stereochemical www.nature.com/scientificreports/ directionality which is formed from the d 10 configuration and a relatively weak nature of the silver(I)-ligand bonds 74 . Hence, the most stable geometrical structure was seen to have a linear geometry 75 as the ground and the excited state energies for this geometrical structure were very stable 76 . In this case, one Ag ion was donated to the Cd 2+ ions.…”
Section: +mentioning
confidence: 97%
“…51 Linear geometry with stable excited state energies was the most stable geometrical structure. 52,53 In this case, Ag + donated an electron to Cd 2+ . As a result of the charge transition from Ag + ions to Cd complexes, the [Cd(NH 3 ) 4 ] 2+ complexes (with a square planar geometry) were transformed into the [Cd(NH 3 ) 4 ] + complex (with a tetrahedral), resulting in the formation of unstable [Ag(NH 3 ) 2 ] 2+ linear complexes.…”
Section: Mechanismmentioning
confidence: 99%
“…32 In this latter case, ammonia forms Ag[NH 3 ] 2 + complexes that deplete the availability of ionic silver in the medium, resulting in quasi-monodisperse silver nanoparticles. 34,35 Although these experiments revealed that the formation of gold nanoparticles is associated with the reducing nature of ammonia formed by the hydrolysis of urea, it is key to highlight that the reduction is considerably quicker in pure reline compared to aqueous urea solutions (a few minutes versus 1.5 h, respectively) despite the fact that urea hydrolysis is favored in the presence of water, as shown in GC analyses of the gases (Figure 4). Such observations reveal the role of choline chloride-based DES in the speciation of the gold precursor with the formation of gold chloro-complexes (e.g., AuCl 4…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…The reducing potential of ammonia is associated with the lone pair of electrons on the nitrogen atom available for donation, and it has been widely used as a reducing agent to synthesize ZnO, CoFe 2 O 4 , and silver nanoparticles . In this latter case, ammonia forms Ag­[NH 3 ] 2 + complexes that deplete the availability of ionic silver in the medium, resulting in quasi-monodisperse silver nanoparticles. , …”
Section: Resultsmentioning
confidence: 99%